Idleness as work? How public defenders do their job by waiting - Ang, Milena (Crime, law and social change, 2023)
How can public defenders provide adequate legal representation when they are underbudgeted and overworked? Mexican public defenders represent 75-90% of those facing a judicial process (either through the entire process or at some points of it) and receive around one tenth of the budget allocated for their counterparts, prosecutors or fiscalías. Drawing from fieldwork conducted in Oaxaca city, Mexicali, and Tijuana, I find that the public defenders spend a considerable amount of time waiting: waiting in the office for their next case to be assigned, waiting to receive a file, or waiting for the judge to show up in court. Although superficially this waiting can be interpreted as idleness, I identify three ways in which defenders do their jobs during their down-time. First, they interchange key information about specific cases with other operators of the system and families and acquaintances of the accused, thus building legal strategies. Second, down time allows them to socialize with agents of the fiscalía, cops, and other courthouse workers, a crucial activity for the establishment of cordial interagency relations. Finally, they also use this down time to do what I call "forced encroachment," meaning the undertaking of activities—such as professionalization of legal translators—that are not necessarily their responsibility but that are nevertheless crucial for the jobs. Waiting, in a way, allows public defenders to provide a legal defense in the absence of time and money to investigate, thus keeping the criminal justice system running.